Gallic acid inhibits neuroinflammation and reduces neonatal hypoxic-ischemic brain damages - Dong, Xiangjun; Luo, Shuyue; Hu, Dongjie; Cao, Ruixue; Wang, Qunxian; Meng, Zijun; Feng, Zijuan; Zhou, Weihui; Song, Weihong (Frontiers in Pediatrics, 2022)
Neuroinflammation is a leading cause of secondary neuronal injury in neonatal hypoxic-ischemic encephalopathy (HIE). Regulation of neuroinflammation may be beneficial for treatment of HIE and its secondary complications. Gallic acid (GA) has been shown to have anti-inflammatory and antioxidant effects. In this report we found that oxygen-glucose deprivation and/reoxygenation (OGD/R)-induced cell death, and the generation of excessive reactive oxygen species (ROS) and inflammatory cytokines by microglia were inhibited by GA treatment. Furthermore, GA treatment reduced neuroinflammation and neuronal loss, and alleviated motor and cognitive impairments in rats with hypoxic-ischemic brain damage (HIBD). Together, our results reveal that GA is an effective regulator of neuroinflammation and has potential as a pharmaceutical intervention for HIE therapy.